Indonesia's G20 Presidency as Middle Power Strategy: Ontological Security, Strategic Narratives, and Global South Leadership - Budi Riyanto; Past Novel Larasaty (Global South Review, 2026)
Indonesia's assumption of the G20 Presidency in 2022, under the thematic banner of 'Recover Together, Recover Stronger,' represented far more than a ceremonial rotation of diplomatic leadership. This article argues that Indonesia's stewardship of the forum constituted a sophisticated expression of middle power diplomacy anchored in ontological security imperatives and deliberate strategic narrative construction. Drawing on qualitative process tracing and interpretive discourse analysis, this study examines how Indonesia leveraged its G20 chairmanship to advance Global South interests while simultaneously reinforcing its self-identity as a non-aligned, development-oriented actor in an increasingly polarized international order. The article demonstrates that Indonesia's diplomatic performance was the product of a coherent strategic narrative calibrated to project credibility, manage competing great power pressures, and secure recognition as a legitimate broker between the industrialized North and the developing South. Theoretically, the study triangulates middle power diplomacy theory, ontological security scholarship, and the strategic narratives framework to offer a more comprehensive analytical lens for understanding Indonesia's foreign policy behavior. The empirical analysis shows that Indonesia's chairmanship successfully established the Pandemic Fund, secured progress on debt restructuring language, and initiated the Just Energy Transition Partnership, thereby validating the efficacy of middle power diplomacy when undergirded by a coherent ontological identity narrative. This study contributes to ongoing debates about the agency of emerging middle powers in shaping global governance architecture and addresses a gap in the literature on the intersection of identity, narrative, and diplomatic strategy among Global South actors.